Analysis of The Disclosure Rate of Local Government Financial Statements in Indonesia - Ayyuuby, Muhammad Al (Universitas Muhammadiyah Surakarta, 2021)
Purpose: One of the criteria for giving an opinion by an examiner according to Act No. 15/2004 is the adequacy of the disclosure rate. Previous research has only examined the disclosure rate partially and has not used data for the 2018 fiscal year. This study aims to analyze the disclosure rate of Local Government Financial Statement (LKPD) for the 2018 fiscal year in Indonesia. Methodology: This study uses a descriptive quantitative approach. The instrument in this study refers to Government Accounting Standards (SAP) based on Government Regulation No. 71/2010 as many as fifteen mandatory criteria consisting of sixty nine sub criteria. The data used in this study is secondary data in the form of Provincial/District/City LKPDs for the 2018 fiscal year as many as 542 LKPDs with saturation sampling technique. Results: The results showed that the level of disclosure in Indonesia is still low at 48.22% with the highest level of disclosure of 65.22% and the lowest level of disclosure of 30.43%. From the analysis of the difference test, it was found that there were differences in disclosure between LKPDs that received unqualified opinions and qualified opinions, there were differences in disclosures between LKPDs that received unqualified opinions and disclaimer of opinions, but there was no difference in disclosure between LKPDs that received qualified opinions and disclaimer of opinions.